Cultura organizacional y bienestar laboral (2018)
This document describes the various processes and elements involved in the construction of the organizational culture of a company and how can it be assimilated by members of the Organization, thereby defining their behavior and contributing to the formation of a working environment appropriate for the development of the employees, in such a way that you will feel comfortable with the company and also motivated to contribute to the achievement of objectives and goals established by the directors and founders of the organization.